Perencanaan Sumber Daya Manusia dan Manajemen Risiko PT Nuno Care Post Partum Depression Pusat Perawatan Pasca Melahirkan - Harahap, Sri Bintang Pamungkas; Negoro, Dimas Angga; Kustiawan, Unggul; Hilmy, Muhammad Reza (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This activity aims to analyze human resource planning and risk management at PT Nuno Care Post Partum Depression, a postpartum care center. Postpartum maternal health services require the support of competent, professional, and empathetic personnel, considering the physical and psychological vulnerability of patients. This PKM method involves mapping needs, training, mentoring, and workshops to prepare documents for the required HR planning. Human resource planning at PT Nuno Care is carried out through the stages of workforce needs analysis, competency-based recruitment and selection, continuous training and development, and employee retention strategies. Meanwhile, risk management includes identifying medical, operational, financial, and reputational risks; analyzing the level of probability and impact; and developing mitigation strategies such as implementing service SOPs, a workforce reserve system, emergency response training, and crisis communication protocols. The integration between human resource planning and risk management has been proven to be mutually reinforcing. Appropriate human resource planning helps minimize operational and medical risks, while the results of risk evaluations provide input for improving human resource strategies. Thus, PT Nuno Care is able to provide safe, comprehensive, and high-quality postpartum services, thereby increasing patient and family trust, while building the company's image as a professional and empathetic postpartum care center.